ARE SHOWROOMING, WEBROOMING, AND CUSTOMER EXPERIENCE EFFECTIVE FOR ONLINE PURCHASE INTENTION? - Widyarini, Lydia Ari; Rommer, Brenda; Kristanti, Maria Mia (Research In Management and Accounting (RIMA), 2025)
Innovation emerges when traditional and online channels are integrated, allowing consumers to utilize both channels simultaneously to satisfy their needs and preferences while also enhancing purchase attraction. The retail industry must therefore adopt omnichannel strategies that provide customers with a seamless consumption experience across physical and digital touchpoints This study examines the effects of perceived showrooming and perceived webrooming on purchase intention in the context of online grocery shopping, with customer experience serving as a mediating variable. To disseminate the findings, this causal research employed purposive sampling and collected data from 170 respondents from various Indonesian provinces who had previously purchased or used an online grocery platform. Data were gathered through a Google Form distributed by the researcher. The analysis was conducted using the Structural Equation Modeling (SEM) technique with SmartPLS as the measurement tool. The results indicate that perceived showrooming and perceived webrooming significantly influence customer experience. Furthermore, perceived showrooming, perceived webrooming, and customer experience all have significant effects on purchase intention.